2011
DOI: 10.1371/journal.pone.0023296
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Female Responses to Conspecific vs. Heterospecific Male Mating Calls in Polygynous Deer: An Open Door to Hybridization?

Abstract: Males of all polygynous deer species (Cervinae) give conspicuous calls during the reproductive season. The extreme interspecific diversity that characterizes these vocalizations suggests that they play a strong role in species discrimination. However, interbreeding between several species of Cervinae indicates permeable interspecific reproductive barriers. This study examines the contribution of vocal behavior to female species discrimination and mating preferences in two closely related polygynous deer specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…This paradigm may work well to find out which signal out of two is more relevant than the other. It has successfully been used in birds [reviewed in Douglas & Mennill, 2010] and frogs [Gerhardt, 1994], and more recently also in deer [Wyman et al, 2011]. Hammerschmidt and Fischer [1998] used this approach to assess infant recognition by female Barbary macaques.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…This paradigm may work well to find out which signal out of two is more relevant than the other. It has successfully been used in birds [reviewed in Douglas & Mennill, 2010] and frogs [Gerhardt, 1994], and more recently also in deer [Wyman et al, 2011]. Hammerschmidt and Fischer [1998] used this approach to assess infant recognition by female Barbary macaques.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…During the reproductive season, both species produce loud and prominent, but acoustically dissimilar, male mating calls, which are thought to be sexually selected. Previous playback experiments found that most oestrous red deer hinds preferred conspecific mating calls over heterospecific sika deer mating calls, although there were individual differences in responses, with some hinds directing more preference behaviours towards heterospecific than conspecific calls (Wyman et al ., ). In this study, we contrast these previous results with similar two‐speaker playback experiments designed to examine the behavioural reactions (preference and attention) of oestrous sika deer hinds to paired presentations of conspecific versus heterospecific male mating calls.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies examining species discrimination of acoustic cues have focused on insects (Doherty & Howard, ; Izzo & Gray, ), anurans (Gerhardt, ; Ryan & Rand, ) and birds (Searcy, ; Derégnaucourt & Guyomarc'h, ). Although a few mammalian studies have examined acoustic species discrimination by males (primates, Mitani, ; Muroyama & Thierry, ; bats, Schuchmann & Siemers, ) or females of unknown reproductive state (primates, Muroyama & Thierry, ), even fewer have examined species discrimination in oestrous females (mice, Meindl, ; deer, Wyman et al ., ). Given complex cognition within mammals, extending recognition studies to this taxon would be highly beneficial to the study of speciation and sexual selection.…”
Section: Introductionmentioning
confidence: 99%
“…While investigations of F0 in the calls of Scottish red deer stags have failed to identify intraspecific correlations between fundamental frequency and body size within populations [28], males with higher minimum F0 have higher reproductive success [28], and playback experiments of resynthesized vocalisations have shown that oestrous females prefer high-pitched roars [42], suggesting that a relatively high pitched voice may be sexually selected for in this subspecies. Moreover, recent playback experiments contrasting the response of oestrous Scottish red deer hinds to homo- or hetero-specific sika deer ( Cervus nippon ) male sexual calls have shown that while red deer females typically prefer their own species vocalisations, a small proportion of individuals appear to prefer high-pitched heterospecific sika moans [12]. We suggest that the positive selection for a high F0 may reflect the fact that in mammals, with a given vocal apparatus, relatively high F0 signals can be produced more efficiently (with a greater intensity) than relatively low F0 signals [64].…”
Section: Discussionmentioning
confidence: 99%
“…The main factors affecting acoustic variation in vocal behaviour are functional (the acoustic structure of signals reflects the type of information they transmit) [7][9], phylogenetic (related species tend to have more similar vocal repertoires [10]–[12], though isolated populations can evolve very different signals) [13], [14] and environmental (the sound propagation properties of the environment in which species live affects their structure [15], [16], as predicted by the “acoustic adaptation hypothesis” [17]). As a consequence, very closely related populations evolving in different habitats can evolve vocalizations which serve the same overall function but which make very different use of the acoustic space [13], [17].…”
Section: Introductionmentioning
confidence: 99%